Ներբող-հանելուկ՝ Սրբոց Թարգմանչացն ու Հայոց գրերի արարմանը - Որսկանյան, Հերիքնազ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В V веке с изобретением армянской письменности было положено начало масштабной просветительской деятельности, в результате которой развились культура и наука, Армянская церковь стала самостоятельной и независимой. Параллельно с переводной литературой было создано одно из первых произведений отечественной агиографии — «Житие Маштоца» Корюна, как хвалебное жизнеописание, ода. Летописцы, вслед за Корюном, перенимают его понимание изобретения письменности одаренной Богом. Начиная с 5 века, история изобретения письменности подвергается национально-духовному переосмыслению. Первая письменная серия армянских загадок (V—VI века) также посвящена национальному письму. Размышления о божественном появлении письменности в серии загадок свое начало берут непосредственно из книги Корюна: письменность и ее предметно-прикладные функции рассматриваются в духовной сфере, с осознанием роли армянской письменности в деле распространения христианства и утверждения новой идеологии в сознании людей. Каждая загадка является важным смысловым звеном в тексте и способствует внутреннему развитию произведения, даже отдельные загадки образуют внутренние группировки по смыслу. Как целостный текст серия загадок в какой-то степени сохранила типологически устойчивые черты жанра оды. Серия загадок — одическое произведение, посвященное письменам. In the 5th century, with the creation of the Armenian alphabet, a large-scale educational activity was launched, which resulted in the development of culture and science; the Armenian Church became independent and autonomous. In parallel with the translated literature, one of the first works of native hagiography, the «Life of Mashtots» by Koryun, was created as a laudatory biography, an ode. The chroniclers following Koryun adopted his comprehension of the creation of the God-given writing. From the 5th century onwards, the history of the creation of writing has undergone a national-spiritual reinterpretation. The first written Armenian riddle series (5th – 6th centuries) is also dedicated to the writing. Reflections on the divine origin of the writing in the riddle series are derived directly from the book of Koryun:writing and its subject-applied functions are considered in the spiritual sphere, with an awareness of the role of the Armenian writing in the spread of Christianity and the establishment of a new ideology in the minds of people. Each riddle is an important semantic link in the text and contributes to the internal development of the work; even individual riddles form internal groupings in terms of meaning. As a coherent text, the riddle series have, to some extent, retained the typologically stable features of the ode genre. The riddle series is odic, dedicated to the writing and expresses the idea of the Holy Trinity: the Armenian word for the writing is made up of three letters symbolizing the Holy Trinity.
Keywords: Բանասիրություն